Odkrivanje nosilcev MRSA v intenzivni enoti - Perme, Janja (Obzornik zdravstvene nege, 2003)
Screening the patients for MRSA at admission may help to early detect MRSA carriers and allow to isolate and decolonize them without delay. With this study at the intensive care unit of the Department of Infectious Diseases we evaluated which cultures sites have the highest detection rate for MRSA. From December 1, 2001 through September 31, 2001 we detected MRSA in 39 from overall 243 hospitalized patients (16%). In 43% of patients we isolated MRSA despite missing previous information about possible colonization or infecrion with MRSA. MRSA was most common found from the throat (49%), nose (41%), and rectum (39%). Rectal swab was approximately 6-times more sensitive than perianal swab. Sputum and tracheal aspirate as well as wound swab were important in patients with wounds or respiratory secretion. MRSA was not foundin urine or from the catheter insertion site. In addition to the nose, throat and rectal swabs represent important specimens for detection of MRSA carriers.
Keywords: Carrier State; Communicable Diseases; diagnostika; infekcije; Infekcijske bolezni; Intensive Care Units; intenzivna nega; Intenzivna oskrba, enote; Klicenoštvo; Methicillin Resistance; Meticilinska rezistenca; Staphylococcus Aureus